Clinical efficacy of 9-oxo-10, 11-dehydroageraphorone extracted from Eupatorium adenophorum against Psoroptes cuniculi in rabbits - Hu, Yang (BMC Vet Res, 2014)
BACKGROUND: Animal acariasis is one of the important veterinary skin diseases. Chemical drugs have been widely used to treat and control this kind of disease. But many chemicals control could increase resistance in target species, toxicity and environmental hazards. We found that the 9-oxo-10, 11-dehydroageraphorone (euptox A) extracted from E. adenophorum has strong toxicity against P. cuniculi in vitro, but the in vivo acaricidal actions of euptox A have yet to be investigated. RESULTS: A 14-day experiment was performed using rabbits that were naturally infested with P. cuniculi on a farm. Rabbits were randomly divided into five groups; animals in groups A, B and C were treated in each ear topically with 4.0 ml of 2.0 and 1.0 g/L (w/v) euptox A, respectively. Animals in groups D and E were treated with ivermectin (by injection; positive controls) and glycerol with water only (by embrocation; negative controls), respectively. Each rabbit was treated twice with separate treatments on days 0 and 7. Rabbits were observed daily and detailed examinations were performed on days 0, 7 and 14, to inspect the presence or absence of mites and scabs/crusts. Seven days after the initial treatment, the mean clinical scores (presence of scabs/crusts) decreased from 3.48, 3.37, 3.43 and 3.45 to 0.37, 0.42, 0.78 and 0.38 in the ears of animals in groups A, B , C and D, respectively, which were similar to the observations recorded in the positive control rabbits. However, the clinical score for negative control rabbits did not increase significantly (P > 0.05) during the experiment, and this changed from 3.32 to 3.37 in the ears, and there were no significant differences in clinical efficacy between left and right ears. After two treatments (0 and 7 d), the rabbits in groups A, B, C and D had recovered completely 14 days after the last treatment and no recurrences of infection were observed. CONCLUSIONS: These results indicate that euptox A was potent compounds for the effective control of animal P. cuniculi in vivo.